Balance prostheses for postural control. - Wall, C., III (IEEE Engineering in medicine and biology magazine)
There is a clear need for a prosthesis that improves postural stability in the balance impaired. Such a device would be used as a temporary aid during recovery from ablative inner-ear surgery and as a permanent prosthesis for those elderly prone to falls. Research using a one-axis device that estimates body tilt and displays it to vestibulopathic subjects via an array of tactile vibrators has demonstrated feasibility. The noninvasive, vibrotactile display of body tilt helped the balance-impaired subjects to reduce their body sway during standardized tests. The motion sensor array is comprised of three MEMS linear accelerometers and three MEMS rate gyros whose sensitive axes are aligned along three orthogonal directions to provide six-degree-of-freedom (dof) motion information.